Learn to Eat and Get a Move On - Calvo, I.; Leão, I.; Nunes, I.; Morgado, J.; Pacheco, R.; Cabaço, T.; Magalhães, T. (Open Schools Journal for Open Science, 2020)
Healthy dieting and the practice of physical activities are deemed fundamental for the adequate growth, development and maintenance of health in young people. This project takes into account these priority areas and is directed towards the educational community, giving a voice to the students through projects such as "Ambassadors of Health" and "E- P@articipate". With "Learn to Eat and Get a Move On" a transversal involvement between community partners, projects and disciplinary areas were achieved, namely through the projects "Mediterranean Diet", "Geodesic Greenhouse" and physical education, with activities being developed in the areas of diet, health and environment. In the greenhouse, aromatic seeds were planted to highlight their importance in a diet, as well as a way to reduce or replace salt.